Management of difficult hepatic artery reconstructions to reduce complications through continual technical refinements in living donor liver transplantations. (August 2022) - Lin, Tsan-Shiun; Lin, Cen-Hung; Kuo, Pao-Jen; Yang, Johnson Chia-Shen; Chiang, Yuan-Cheng; Li, Wei-Feng; Wang, Shih-Ho; Lin, Chih-Che; Liu, Yueh-Wei; Yong, Chee-Chien; Chen, Chao-Long; Cheng, Yu-Fan; et al.
Abstract: Background: Hepatic artery reconstruction (HAR) for liver transplantation is crucial for successful outcomes. We evaluated transplantation outcome improvement through continual technical refinements. Materials and methods: HAR was performed in 1448 living donor liver transplants by a single plastic surgeon from 2008 to 2020. Difficult HARs were defined as graft or recipient hepatic artery ≤2 mm, size discrepancy (≥2 to 1), multiple hepatic arteries, suboptimal quality, intimal dissection of graft or recipient hepatic artery (HA), and immediate redo during transplantation. Technique refinements include early vessel injury recognition, precise HA dissection, the use of clips to ligate branches, an oblique cut for all HARs, a modified funneling method for size discrepancy, liberal use of an alternative artery to replace a pathologic HA, and reconstruction of a second HA for grafts with dual hepatic arteries in the graft. Results: Difficult HARs were small HA (21.35%), size discrepancy (12.57%), multiple hepatic arteries (11.28%), suboptimal quality (31.1%), intimal dissection (20.5%), and immediate redo (5.18%). The overall hepatic artery thrombosis (HAT) rate was 3.04% in this series. The average HAT rate during the last 4 years (2017–2020) was 1.46% (6/408), which was significantly lower than the average HAT rate from 2008 to 2016 (39/1040, 3.8%) with a statistical significance (p = 0.025). Treatment for posttransplant HAT included anastomosis after trim back (9), reconstruction using alternatives (19), and nonsurgical treatment with urokinase (9). Conclusion: Careful examination of the HA under surgical microscope and selection of the appropriate recipient HA are key to successful reconstruction. Through continual technical refinements, we can reduce HA complications to the lowest degree. Highlights: Recognition of injuries, precise dissections and use of hemoclips to ligate branches are important for a successful HAR. Immediate redo hepatic artery reconstruction should be carried out while the flow is less than 0.30 m/s. Oblique cut method for size discrepancies less than 2 to 1 while modified funneling method for greater discrepancy. The right gastroepiploic artery is the most adopted alternative to replace a pathological hepatic artery.